A systematic review on the efficacy of vitamin D supplementation on diabetic peripheral neuropathy. Issue 10 (October 2020) - Yammine, Kaissar; Wehbe, Rudy; Assi, Chahine
Summary: Background & aims: Vitamin D deficiency is known to be prevalent in patients with diabetes and in particular in those having symptoms of diabetic peripheral neuropathy (DN). Thus, it is worthy to investigate whether a supplementation of vitamin D would improve pain among those having diabetes and DN. Methods: A systematic literature search was performed to identify studies that reported the impact of vitamin D supplementation on the signs and symptoms of DN. Random effect models were used to meta-analyze effect sizes. Quality assessment was also performed. Results: Four studies including 364 patients met the inclusion criteria. Meta-analytical results were as follows: Serum Vitamin D level change of 1.39 (95% CI = 1.220 to 1.573, p = 0.008), HbA1c change of 0.134 (95% CI = −0.153 to 0.418, p = 0.3), McGill Pain Questionnaire score of 1.14 (95% CI = 1.222 to 1.672, p < 0.0001), all in favor of the vitamin D supplementation group. Non-meta-analytical results of all individual studies showed significant amelioration of pain scores. One study reported no significant change in nerve conduction study. Pain improvement was not correlated to baseline or change in serum vitamin D level. Conclusion: Vitamin D supplementation could be an added value in the treatment of painful peripheral diabetic neuropathy. Amelioration in pain might be related to the absolute value of vitamin D attained following supplementation. The findings of this review are promising and further research with large sample randomized trials is warranted.